Implementasi Teknologi QR Code pada Sistem Absensi Karyawan Berbasis Website - Nanda Aprillia, Monita; Wahyu Christanto, Febrian; Parga Zen, Bita; Maulana, Haisyam; Yudi Permana, Nana (Jurnal Sistem Informasi Galuh, 2025)
Traditional attendance systems face challenges related to their vulnerability to human error and limitations in management time. Using a QR Code provides attendance management and recording benefits. The problem that occurred at the Jati Mulya Shop in January - June 2024 was that there were 5 employees who manipulated attendance, causing losses.  Jati Mulya Shop is a fashion shop that has a good reputation and has quite a large number of employees located at Pasar Johar Semarang. The aim of this research is to implement web-based QR Code attendance. The data source in this research is primary data in the form of interviews with business owners. The system development method used is the Prototype model. Before implementing the QR code-based attendance system, Jati Mulya Shop experienced a loss of Rp. 2,810,000 per month, consisting of Rp. 2,500,000 due to absence without permission and Rp. 310,000 due to errors in recording absences. After implementing the new system, efficiency increased 100% so that the loss became Rp. 0. With the QR code system, unauthorized absences and errors in recording absences as well as financial losses are completely eliminated. The hope created by this system can make it easier for business owners to monitor employees and employees who are often absent will also be helped by this system.